Desenvolvimento de plantas de maracujazeiro-amarelo produzidas por enxertia hipocotiledonar em cinco porta-enxertos de passifloras silvestres - Filho, Geraldo Costa Nogueira; Roncatto, Givanildo; Ruggiero, Carlos [UNESP]; de Oliveira, João Carlos [UNESP]; Malheiros, Euclides Braga [UNESP] (My University, 2010)
The experiment was carried out in an area of a small producer supplier of Maguari (Kraft Foods of Brazil) in Araguari-MG, and aimed to assess the development of yellow passion fruit plant grafted on five rootstocks of native passifloraceas using the hypocotyledonary grafting method. The treatments used as rootstocks were P. edulis f. flavicarpa, P. caerulea, P. alata, P. gibertii and P. cincinnata. The yellow passion fruit non-grafted seedlings were used as control, completing six treatments. For all treatments, the yellow passion plant FB 200 was used as canopy crown variety. It was used the experimental design randomized blocks with three repetitions. The plot was formed by a line of 20 meters long containing four plants. The passion fruit planting was done according to cultural treatments recommended for this culture. The characteristics evaluated were plant height, number of leaves, diameter of the region of grafting, the scion diameter, diameter of the rootstock, relation between scion and rootstock. The plants of P. edulis f. flavicarpa, P. caerulea and the non-grafted seedlings showed better development. Plants of the rootstock P. alata had the worst development. Although the non-grafted seedlings have exceeded the development of grafted with P. cincinnata e P. gibertii, they did not differ significantly from them, and the rootstock P. alata negatively influenced on the plant height, number of leaves, diameter of the region of grafting, the graft diameter, diameter of the rootstock, relation between scion and rootstock.
Development of yellow passion fruit plant produced by hypocotyledonary grafting on five rootstocks of wild passiflora in araguari-MG
Keywords: Agronomic performance; Passiflora spp; Vegetative propagation